Journey of the pharaohs (NUMA files, 17,, 2020)
"Kurt Austin and the NUMA crew race to identify a link between an ancient Egyptian treasure, a 1927 daredevil aviator's disappearance and the sinking of a modern fishing trawler to prevent a scheme by a cutthroat arms dealer."--

Fast ice: a novel from the NUMA files (NUMA files, 18,, 2021)
In the early days of World War II, the infamous German Luftwaffe embark upon an expedition to Antarctica, hoping to set up a military base to support their goal of world domination. Though the military outpost never comes to fruition, what the Nazis find on the icy continent indeed proves dangerous...and will have implications far into the future. In the present day, Kurt Austin and his assistant Joe Zavala embark for the freezing edge of the world after a former NUMA colleague disappears in Antarctica. While there, they discover a photo of the Luftwaffe expedition of 1939, and are drawn into a decades-old conspiracy. Even as they confront perilous waters and frigid temperatures, they are also are up against a terrifying man-made weapon--a fast-growing ice that could usher in a new Ice Age.

Fast ice (NUMA files, 18,, 2021)
In the early days of World War II, the infamous German Luftwaffe embark upon an expedition to Antarctica, hoping to set up a military base to support their goal of world domination. Though the military outpost never comes to fruition, what the Nazis find on the icy continent indeed proves dangerous ... and will have implications far into the future. In the present day, Kurt Austin and his assistant Joe Zavala embark for the freezing edge of the world after a former NUMA colleague disappears in Antarctica. While there, they discover a photo of the Luftwaffe expedition of 1939, and are drawn into a decades-old conspiracy. Even as they confront perilous waters and frigid temperatures, they are also are up against a terrifying man-made weapon--a fast-growing ice that could usher in a new Ice Age. Pitted against a determined madman and a monstrous storm, Kurt and the NUMA team must unravel the Nazi-era plot in order to save the globe from a freeze that would bury it once and for all.

The storm (NUMA files, 10,, 2012)
Kurt Austin and Joe Zavala investigate the smoldering hulk of a NUMA research vessel in the Indian Ocean and soon uncover an audacious scheme to permanently alter the weather on a global scale, killing millions.